PENGARUH HUKUM INTERNASIONAL TERHADAP PERKEMBANGAN HUKUM KONTRAK DI INDONESIA - Putri Oktaviani Yulias; Ratri Yulianingsih; Maya Nurantika; Jenny Meriam Berlina Sihombing; Budi Ardianto (Cahaya Ilmu Bangsa, 2024)
International law as rules of law relating to individuals and non-state bodies, the rights and obligations that turned out to be important for the international community is international trade. International trade in general evolve towards freer trade and open. The presence of the World Trade Organization (WTO), and cooperated with other trade cooperation such as AFTA, APEC, even in the current developments in the region such as the AEC, resulting in world trade pushed towards freer trade and open. Trade through forms of cooperation, it is also cultivated free from unfair business practices so that it can evolve into a more conducive climate, therefore, to anticipate these developments, in addition to the use of a means of protection which are public, business people should also carry out protection in ways that are self-protection as business interests through contract law. The principle of freedom of contract as provided for in Article 1338 of the Civil Law Consequences to bring new contract models that were previously unknown in treaty law in Indonesia. The new contracts also cover the affected areas of the construction of the Federation Internationale des Ingénieurs Counsels (FIDIC), American Institute of Architects (AIA), Joint Contract Tribunals (JCT), Singapore Institute of Architects (SIA)